Structure and Mechanical Properties of a Titanium–8 wt.% Gallium Alloy - David W. Wheeler (Crystals)
This paper describes a study of the microstructure and mechanical properties of a titanium–gallium (Ti-8 wt.% Ga) alloy using X-ray diffraction, optical metallography, micro-hardness measurements, compression and tensile testing, nanoindentation and ultrasonic velocity measurements. X-ray diffraction has shown the alloy to be wholly α Ti with no other phases present. A comparison of the hardness and elastic modulus values of the Ti-8Ga alloy with those of Ti-6Al-4V showed the former to have a significantly higher hardness, although the elastic moduli of the two alloys were broadly comparable. The study also indicated reasonable agreement between the elastic moduli obtained by nanoindentation, ultrasonic velocity measurements and tensile testing. Under compressive loading, the mean 0.2% proof stress values of the Ti-8Ga alloy were between 1066 MPa and 1083 MPa. However, under tensile conditions, the mean tensile strength was found to be only 427 MPa, and the alloy exhibited highly brittle behaviour, with specimens failing before they had undergone any appreciable plasticity. The cause of this was ascribed to high oxygen and nitrogen levels.